Letter (copy) : Foodstuffs for Spain - Citrine, Walter, 1887-1983
029-0076-001 EMC/HVT/FC/101. Secretary's. 18th December, 1937. Mr W. Schevenels, The International Federation of Trade Unions, 9 Avenue D'orsay PARIS, VIIe. Dear Mr. Schevenels, FOODSTUFFS FOR SPAIN. Referring to your letter of the 17th instant I am very sorry to inform you that owing to difficulties of war risks it has not been possible to complete arrangements for the sailing of the s.s. "Hartbridge". The master has refused to sign the Bills of Lading and the whole position is being gone into this week-end. I hope to write you again on Monday when I trust I shall have better news. Yours sincerely, General Secretary. 292/946/29/76